KEPERCAYAAN DIRI PEMBELAJAR PADA MATEMATIKA (Suatu Kajian Teoritik) - Jailani, Jailani (Jurnal Cakrawala Pendidikan, 1999)
Many factors affect learners' performance in learningmathematics. One is self-confidence, which is an importanttopic for discussion. Some researches have revealed thatlearners whose self-confidence is high have a low level ofanxiety in mathematics and vice versa. ..Learners' self-confidence in mathematics is their ownperception about their ability or competence in doing mathematics(e.g., in studying or doing tests on mathematics).Studies on genius reveal that most successfil original thinkershave been characterized with a high degree of self-confidence.Self-confidence can contribute to learners' achievenient,Improvements on learners' self-confidence can be doneby shoring up their self-image, self-esteem, and self-worth.especially when they fail their mathematics examination orbecome the objects of others' mockery or pressure.